Banks' risk culture and management control systems: A systematic literature review - Jennifer Kunz; Mathias Heitz (Journal of Management Control, 2021)
Over ten years of a debate about the best ways to make banks safer have led to the conclusion that improving their risk culture is one venue to achieve this goal. Consequently, different disciplines discuss topics related to risk culture from varying methodological angles. This effort of many scholars provides a rich basis of theoretical and empirical evidence to guide business practice and improve regulation. However, the application of many approaches and methods can result in fragmentation and loss of a comprehensive perspective. This paper strives to counteract this fragmentation by providing a comprehensive perspective focusing particularly on the embeddedness of risk culture into banks' management control systems. In order to achieve this goal, we apply a systematic literature review and interpret the identified findings through the theoretical lens of management control research. This review identifies 103 articles, which can be structured along three categories: Assessment of risk culture, relation between risk culture and management controls (with the subcategories embeddedness of risk culture in overall management control packages, risk culture and cultural controls, risk culture and action controls, risk culture and results controls, as well as risk culture and personnel controls) and development of banks' risk culture over time. Along these categories the identified findings are interpreted and synthesized to a comprehensive model and consequences for theory, business practice and regulation are derived.
Keywords: D81; D91; M14; M38; M48; 330; Management control systems; Risk culture; Risk climate; Systematic literature review